Deixis Found in the Movie "12 Strong" by Nicolai Fulgsig - Dita Marwati; Ambalegin Ambalegin (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
The theory used in this research was proposed by Yule, (1996) to analyze deixis found in the movie. “12 Strong” movie by Nicolai Fuglsig will be the data source to analyze deixiz. This research will be focused on the deixis from the utterances that uttered by the characters in the movie. The research will be used descriptive qualitative method of the research to conduct the data. The researchers will be analyzed the utterances which uttered from the characters in the movie “12 Strong.” The utterances discovered in the movie will be classified used theory types of deixis proposed by (Yule, 1996) which were person deixis, spatial deixis, and the last is temporal deixis. The observational method and non-participatory technique as the method of collecting the data will be used in this research. The result will be discovered that there were 15 utterances of deixis uttered by the characters in the movie. They are included 5 data discovered as person deixis, 6 data discovered as spatial deixis, and 4 data discovered as temporal deixis. The spatial deixis was more often used in the utterances found in the movie.